(untitled) (Iranian Journal of Kidney Diseases, 2021)
Small vessel necrotizing vasculitis is divided into two groups; Immune complex mediated and Pauci immune vasculitis. Hemolytic uremic syndrome (HUS) is a rare disease manifested as microangiopathic hemolytic anemia, thrombocytopenia and renal involvement. The coexistence of ANCA negative vasculitis and atypical HUS (aHUS) is rare. We describe a case of a 40 years old lady with rapidly declining kidney function. Renal Biopsy revealed Crescentic necrotizing glomerulonephritis (CGN). She was treated with plasmapheresis alternating with hemodialysis (HD) and immunosuppressive therapy. One month later she developed hemolytic anemia with peripheral schistocytes and thrombocytopenia and diagnosed as aHUS. Same treatment continued and her aHUS resolved spontaneously over one week. However her kidney functions didn’t improve and ended up with end stage renal disease (ESRD). DOI: 10.52547/ijkd.6443